On-farm soybean genetic progress and yield stability during the early 21st century: A case study of a commercial breeding program in Argentina and Brazil - Abdala, Lucas J.; Otegui, María Elena; Di Mauro, Guido (Elsevier, 2024)
CONTEXT: Most studies assessing the genetic progress in soybean have traditionally focused on retrospectives approaches, where commercial genotypes released over an extended period are tested in a limited number of environments. In this context, multi-environment trials (METs) from a soybean breeding program constitute an interesting approach to complement previous studies. OBJECTIVE: This study aims to quantify the rate of genetic progress in soybean genotypes developed by the private seed company Grupo Don Mario in Argentina and Brazil. Our objective was to estimate breeding effects on yield and yield stability across maturity groups (MGs) and to analyze how these effects have been affected across yield environments. METHODS: We studied 124 soybean genotypes from MGs IV to VIII in 2015 METs. Genotypes were released from 2005 onwards in Argentina and from 2010 onwards in Brazil. To assess breeding effects, genotype seed yield best linear unbiased predictor (BLUP), yield stability, and the genotype BLUP in low, medium, and high yielding environments were regressed to the year of release. RESULTS: Seed yield genetic progress was evident for all MGs and ranged from 20.5 to 46.1 kg ha−1 yr−1 in Argentina and from 23.2 to 53.6 kg ha−1 yr−1 in Brazil. Moreover, no changes were observed for yield stability during recent years. When dissecting the genetic progress by targeted environment yield, the rate in Argentina was 41.4, 23.6, and 16.6 kg ha−1 yr−1 in the high, medium, and low yielding environment, with relative rates of 0.9%, 0.6% and 0.6% yr−1, respectively. In Brazil, the rate was 43.0, 40.5, and 17.8 kg ha−1 yr−1 in the high, medium, and low yielding environment, with relative rates of 0.9%, 1.0% and 0.5% yr−1, respectively. Absolute and relative rates increased from low to high environmental quality. However, the rate varied across MGs and environmental yield. CONCLUSIONS: Our study revealed that, while genetic progress was evident for MG IV to VII in Argentina and for MG V to VIII in Brazil, most genotypes did not change their response to improvements in environmental quality during the early 21st century. Moreover, the rate of progress depended on the interaction between MGs and environmental yield. IMPLICATIONS: This study complements retrospective estimates of soybean genetic progress by evaluating a broader range of environments and MGs. Future research should focus on exploring the physiological and/or environmental factors behind the different rate of progress across MGs and yield environments.